Turnover intention of young graduates in Singapore. - Loo, Victor Shui Fong. (2009)
This study was undertaken to investigate the factors that influence young university graduates in their intention to resign from a job. With this study, we hope that employers will be better positioned to introduce the relevant measures to retain these valuable human resources in their organisations by creating more conducive working environments.